1990
DOI: 10.1161/01.hyp.16.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated natriuretic response to atrial natriuretic factor in rats developing spontaneous hypertension.

Abstract: The present study was designed to evaluate the renal response to atrial natriuretic factor (ANF) in young rats developing spontaneous hypertension (SHR) and compare this response to age-matched, normotensive controls (WKY) and adult animals. At 6 weeks of age, intravenous infusion of ANF (0.25 /tg/kg min) in anesthetized, euvolemic rats produced a significantly larger natriuresis and diuresis in SHR compared with WKY rats; this strain difference was not observed in rats 11 weeks of age. SHR showed no age-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Indeed, ANP appears to be a key candidate among potential factors involved in the pathogenesis of hypertension -likely due to the essential role of the kidney and renal function in the development of hypertension, and the effects of ANP on natriuresis, diuresis and hypertension itself [9]. Animal models have demonstrated an exaggerated diuretic and natriuretic response to exogenously administered ANP in spontaneously hypertensive rats compared with normotensive strains [82]. Furthermore, genetically reduced production of ANP has been shown to lead to salt-sensitive hypertension in mice [83].…”
Section: Hypertensionmentioning
confidence: 99%
“…Indeed, ANP appears to be a key candidate among potential factors involved in the pathogenesis of hypertension -likely due to the essential role of the kidney and renal function in the development of hypertension, and the effects of ANP on natriuresis, diuresis and hypertension itself [9]. Animal models have demonstrated an exaggerated diuretic and natriuretic response to exogenously administered ANP in spontaneously hypertensive rats compared with normotensive strains [82]. Furthermore, genetically reduced production of ANP has been shown to lead to salt-sensitive hypertension in mice [83].…”
Section: Hypertensionmentioning
confidence: 99%
“…SHR have been shown to exhibit higher systolic blood pressure (BP) than Wistar-Kyoto rats (WKY) at 3 weeks, 6 4 1 ⁄2 weeks, 7 and 5 weeks of age 8 -10 ; SHR have also shown higher systolic BP than at 6 weeks, [11][12][13] 7 weeks, 14,15 9 weeks, 14 -16 10 weeks, 17 and 12 weeks of age. 18 -20 Similarly, reports on ANF and BNP production and secretion in hypertension are controversial and have been carried out mostly in male SHR at a time when hypertension and left ventricular hypertrophy were already established (Ͼ 17 weeks).…”
mentioning
confidence: 99%
“…However, in kidneys from young prehypertensive SHRs (3-4 wk), renal GLP-1R expression was significantly diminished, as judged by immunohistochemistry, despite normal expression in the pancreas. At 6 wk of age, arterial blood pressure in SHRs was slightly increased compared with agematched WKY rats (31), and no differences were found in RBF and GFR, suggesting that at this young age, the SHR is hemodynamically comparable to the WKY rat. However, another study (13) showed that at 6 wk of age, SHRs had significantly decreased RBF and GFR, which could contribute to the development of hypertension in these animals.…”
Section: Discussionmentioning
confidence: 80%